2024
DOI: 10.1186/s13018-024-04646-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the in vitro antibacterial efficacy of composite bone cement incorporating natural product-based monomers and gentamicin

Yu-Chen Kan,
Rui Guo,
Yang Xu
et al.

Abstract: Objective The objective of this study is to investigate the impact of four natural product extracts, namely, aloe-emodin, quercetin, curcumin, and tannic acid, on the in vitro bacteriostatic properties and biocompatibility of gentamicin-loaded bone cement and to establish an experimental groundwork supporting the clinical utility of antibiotic-loaded bone cements (ALBC). Methods Based on the components, the bone cement samples were categorized as f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Gentamicin sulfate is an aminoglycoside antibiotic used mainly to deal with bone infections due to its relatively broad antimicrobial spectrum and high thermostability. ,, Research by Nichol et al revealed that the addition of gentamicin to a monolayer organic–inorganic hybrid sol–gel coating completely eradicated planktonic bacteria as well as biofilms of a panel of clinically relevant staphylococci, while such a coating did not interfere with bone healing . Likewise, high- and long-term doses of gentamicin can trigger serious adverse reactions in the surrounding nerves, so it is important to choose only the necessary concentration of the drug for the given time . Since bacterial colonization usually occurs in the first hours after material implantation, short-term systemic prophylaxis is as effective as long-term prevention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gentamicin sulfate is an aminoglycoside antibiotic used mainly to deal with bone infections due to its relatively broad antimicrobial spectrum and high thermostability. ,, Research by Nichol et al revealed that the addition of gentamicin to a monolayer organic–inorganic hybrid sol–gel coating completely eradicated planktonic bacteria as well as biofilms of a panel of clinically relevant staphylococci, while such a coating did not interfere with bone healing . Likewise, high- and long-term doses of gentamicin can trigger serious adverse reactions in the surrounding nerves, so it is important to choose only the necessary concentration of the drug for the given time . Since bacterial colonization usually occurs in the first hours after material implantation, short-term systemic prophylaxis is as effective as long-term prevention.…”
Section: Introductionmentioning
confidence: 99%
“… 26 Likewise, high- and long-term doses of gentamicin can trigger serious adverse reactions in the surrounding nerves, so it is important to choose only the necessary concentration of the drug for the given time. 27 Since bacterial colonization usually occurs in the first hours after material implantation, short-term systemic prophylaxis is as effective as long-term prevention. In fact, a short-term local drug delivery system can meet the requirements to prevent local infection while limiting possible long-term adverse side effects.…”
Section: Introductionmentioning
confidence: 99%